A high-yield vacuum-evaporation-based R2R-compatible fabrication route for organic electronic circuits - Patchett, E; Williams, A; Ding, Z; Abbas, G; Assender, H; Morrison, J; Yeates, S; Taylor, D (Elsevier, 2014)
Advances are described in a vacuum-evaporation-based approach for the roll-to-roll (R2R) production of organic thin film transistors (TFTs) and circuits. Results from 90-transistor arrays formed directly onto a plasma-polymerised diacrylate gate dielectric are compared with those formed on polystyrene-buffered diacrylate. The latter approach resulted in stable, reproducible transistors with yields in excess of 90%. The resulting TFTs had low turn-on voltage, on-off ratios ∼106 and mobility ∼1 cm2/V s in the linear regime, as expected for dinaphtho[2,3-b: 2′,3′-f] thieno[3,2-b]thiophene the air stable small molecule used as the active semiconductor. We show that when device design is constrained by the generally poor registration ability of R2R processes, parasitic source-drain currents can lead to a >50% increase in the mobility extracted from the resulting TFTs, the increases being especially marked in low channel width devices. Batches of 27 saturated-load inverters were fabricated with 100% yield and their behaviour successfully reproduced using TFT parameters extracted with Silvaco's UOTFT Model. 5- and 7-stage ring oscillator (RO) outputs ranged from ∼120 Hz to >2 kHz with rail voltages, VDD, increasing from -15 V to -90 V. From simulations an order of magnitude increase in frequency could be expected by reducing parasitic gate capacitances. During 8 h of continuous operation at VDD = -60 V, the frequency of a 7-stage RO remained almost constant at ∼1.4 kHz albeit that the output signal amplitude decreased from ∼22 V to ∼10 V. Over the next 30 days of intermittent operation further degradation in performance occurred although an unused RO showed no deterioration over the same period. © 2014 The Authors. Published by Elsevier B.V.